2020
DOI: 10.1177/1535370220936150
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound cavitation enhanced chemotherapy: In vivo research and clinical application

Abstract: Ultrasound and microbubbles can induce apoptosis of tumor cells. However, the effects of ultrasound and microbubbles (USMB) combined with chemotherapy on in vivo tumors have rarely been studied. This research is to evaluate the efficacy of targeted USMB and chemotherapeutic drugs on apoptosis and inhibition of hepatic carcinoma cells in nude mice. We also summarize case reports of its clinical application. It was divided into three parts: First, the subcutaneous hepatic tumors of nude mice were irradiated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…These holes generate a cellular response to reseal them, and if the damage induced by the ultrasound-stimulated microbubbles (USMB) is sufficiently large, the cells will die as a result of their microbubble-induced injuries [ 58 , 59 ]. The effects of USMB on tumour vasculature have been shown to facilitate an enhanced sensitivity towards chemotherapy [ 60 , 61 , 62 ] and radiation therapy (XRT) [ 63 , 64 , 65 ]. The safety of using USMB in clinical settings has already been established for the treatment of several diseases; however, the idea of utilizing USMB as a therapeutic agent for cancer has only recently been looked into.…”
Section: Introductionmentioning
confidence: 99%
“…These holes generate a cellular response to reseal them, and if the damage induced by the ultrasound-stimulated microbubbles (USMB) is sufficiently large, the cells will die as a result of their microbubble-induced injuries [ 58 , 59 ]. The effects of USMB on tumour vasculature have been shown to facilitate an enhanced sensitivity towards chemotherapy [ 60 , 61 , 62 ] and radiation therapy (XRT) [ 63 , 64 , 65 ]. The safety of using USMB in clinical settings has already been established for the treatment of several diseases; however, the idea of utilizing USMB as a therapeutic agent for cancer has only recently been looked into.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound targeted microbubble destruction (UTMD) or USMB has been widely used in promoting chemotherapy of various experimental solid tumors (Todorova et al, 2013 ; Kotopoulis et al, 2014 ; Ingram et al, 2020 ; Shen et al, 2020 ; Xia et al, 2021 ). For these studies, local drug concentration and tumor growth inhibition were the primary concerns because they are directly related to major therapeutic effects in a clinical context (Kurdziel et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Low-intensity ultrasound, as a safe and noninvasive treatment, has been widely used in cancer treatment [ 14 , 15 ]. As one of the important effects of ultrasound biology, ultrasound cavitation significantly inhibits tumor cell proliferation and formation mainly through the mechanical effects and cavitation effects produced by ultrasound [ 14 , 16 ]. Studies have shown that ultrasound microbubble contrast agents can significantly enhance the cavitation effect produced by low-frequency and reduce the cavitation threshold, indicating that low-frequency ultrasound-stimulated microbubbles (USMB) has a significant inhibitory effect on tumor cell growth [ 17 ].…”
Section: Introductionmentioning
confidence: 99%